ANALISIS FAKTOR – FAKTOR KELELAHAN KERJA PEKERJA MEBEL CV X DI KOTA SEMARANG - Fifi Harlinda; Baju Widjasena; Bina Kurniawan (Jurnal Kesehatan Masyarakat, 2023)
The furniture industry is one of the growing informal sector businesses. Public demand for furniture is so great that many furniture production facilities have sprung up. Work fatigue is one of the occupational safety and health problems that is a factor causing accidents at work. One of the potential hazards in this industry is posture, an uncomfortable work environment that will result in decreased performance. From the initial interviews conducted with 4 workers, there were 4 workers complaining of work fatigue caused by one of them being ergonomic and then making a difference in the worker's body posture. There are 5 activities for making furniture, namely rough sanding, fine sanding, assembly, welding and finishing. This study was to analyze the causes of work fatigue in CV X furniture workers in Semarang City. This study uses a descriptive qualitative method with an observational approach and is carried out by assessing work posture factors with REBA worksheets and using a reaction timer in August 2022. The main informants involved are 5 workers representing each work activity, while the triangulation informants are 2 people. Research results Based on observations using the REBA method, there are 40% (2 postures) with medium risk (medium risk), 40% (2 postures) with high risk (high risk) and 20% (1 posture) with very high risk (very high risk). high risk). There is a work posture that is immediately investigated and exposed to changes from an ergonomic work position so that there are no work-related diseases or work accidents.